#TITLE_ALTERNATIVE# - LUTHFIANA FAJRI (NIM 10105024), LISHA
Oil is a nonrenewable natural resource. Its usage in industrial and daily life causes oil field explored and produced high rate. And highly methods are needed. A decrease of oil production is an important concern thing on reservoir management. If production reached critical economic value, the production of that well are not productive anymore. Decline Curve Analysis (DCA) is one of estimation methods that used to predict a well-productive-period. This method used last five year production data. The object of this research is production well W-18 Tambun-Bekasi field. In this final project, we explained how Arps models are used to develop a DCA of oil production. Hyperbolic models are approximated by binomial expansion, Taylor expansion, and Nonlinear Least Squares (NLS). Case studies showed that further developments are needed to obtain a better model.